Central bank Digital Currencies: Key Characteristics and Directions of Influence on Monetary and Credit and Payment Systems - D. A. Kochergin; A. I. Yangirova (Финансы: теория и практика, 2019)
The article is devoted to the study of prospects for digital currency issue by central banks as a new form of central bank money and to the potential of their influence on monetary and credit system. The aim of the article is to interpret and classify central bank digital currencies, to identify key characteristics of digital currencies and possible models of their issue, as well as to define the main directions of influence of digital currencies on the monetary and credit and payment systems. The scientific novelty of the article is in the systematization and comparison of different ideas about the implementation of sovereign digital currencies considering the use of distributed registry technologies. The study analyzed the projects of central banks on the issue of digital currencies and identified their features. Possible directions of influence of central bank digital currencies on the monetary and credit policy of the Central Bank and the activities of credit institutions were determined. It revealed that central bank digital currencies can be considered as a new form of money of the Central Bank, which can be issued to be used both in retail and in wholesale payments. Digital currencies may differ in some characteristics. The key ones are: a way to integrate into the monetary and credit system; emission technology; currency storage method; mechanism of mutual settlements and anonymity level. The study showed that the main incentives for introducing digital currencies are the possibility to provide an alternative and universally accessible legal means of payment, as well as to provide faster, more transparent and cheaper in-country and cross-border payments. The influence of digital currencies on the monetary and credit system and the monetary and credit policy of the Central Bank will largely depend on the scenario of their system integration. If cash is simply replaced in circulation by digital currencies, the effect on the Central Bank monetary and credit system and policy will not be significant. However, if central bank digital currencies are issued as an addition to cash, or are in parallel circulation, they can strengthen the transmission mechanism of the monetary and credit policy and increase the centralization of assets on the Central Bank balance sheet, as well as reduce the funding provided by credit institutions.